The Effect of Derivative Hedging Policy on Cash Flow Volatility and Financial Performance in Export-Oriented Companies - Ekayana Sangkasari Paranita; Sapto Haji (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study analyzes the impact of derivatives hedging policies on cash flow volatility and the financial performance of export-oriented companies. Export companies face significant risks due to fluctuations in exchange rates and global market uncertainties, which affect their cash flows and overall financial stability. To mitigate these risks, companies often adopt derivatives hedging strategies, utilizing instruments such as forward contracts, futures, options, and swaps. This research adopts a Systematic Literature Review (SLR) approach, where a structured search and synthesis of relevant journal articles, academic books, and reports were performed to gather existing insights on derivatives hedging in export companies. The findings from the literature suggest that derivatives hedging policies are effective in reducing cash flow volatility and improving financial performance by providing stability in cash flows and mitigating risks associated with exchange rate fluctuations. However, the effectiveness of these hedging strategies is contingent on selecting appropriate instruments and aligning them with the company’s risk profile. This study also highlights the challenges posed by transaction costs and the complexity of implementing hedging policies. The research contributes to understanding how derivatives hedging policies can assist companies in managing external risks, and it offers recommendations for future research to explore the comparative effectiveness of various derivative instruments in enhancing the financial performance of companies across different sectors.